2012
DOI: 10.1116/1.4764049
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of epitaxially grown indium islands on Si(111)

Abstract: Indium deposition onto on-axis Si(111) substrates and those miscut by 2.5° toward [112¯] was investigated. The Si substrates were held at temperatures ranging from room temperature up to 475 °C and the In deposition rate was varied by a factor of ∼20. All depositions were performed under ultrahigh vacuum conditions onto surfaces that were cleaned in situ. For growth at 100 °C and room temperature, the In films organize into three-dimensional islands. This result suggests that In deposition onto on-axis or misc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Previous results published by our group and others have shown that In growth on Si(111) at temperatures lower than the In melting point (156 °C) follows the Stranski− Krastanov (SK) mode for which 3D islands grow atop a thin planar layer. 43,44 Therefore, it is likely that the 3D islands observed in Figure 2a are the outcome of this growth mode. That is, the 3D islands form during room temperature In deposition and persist after selenization.…”
Section: Resultsmentioning
confidence: 97%
“…Previous results published by our group and others have shown that In growth on Si(111) at temperatures lower than the In melting point (156 °C) follows the Stranski− Krastanov (SK) mode for which 3D islands grow atop a thin planar layer. 43,44 Therefore, it is likely that the 3D islands observed in Figure 2a are the outcome of this growth mode. That is, the 3D islands form during room temperature In deposition and persist after selenization.…”
Section: Resultsmentioning
confidence: 97%
“…The major reason is that high quality III-V semiconductor materials can be directly grown on it [1,2,3]. This enables great possibilities of monolithic integration of the III-V devices (as well as optoelectronic and microelectronic devices) with silicon devices [4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%